Analyzing the Economic and Legal Impacts of Foreign Vessel Dominance in Indonesia's Trade Activities - Najmah Ramadhani Syukur; Ade Siti Ardila; Nanna Daun Tasik; Halisah; Erlin Aulia Ningsih (Punggawa Global Research: Jurnal Multidisiplin, 2026)
This study analyzed the economic and legal impacts of foreign vessel dominance in Indonesia's international trade and evaluated the effectiveness of maritime regulation in strengthening the national shipping industry. Using normative legal research that combined statutory and conceptual approaches, the study examined relevant maritime legislation, trade data, and law-enforcement mechanisms. The findings revealed a striking paradox in the implementation of the cabotage principle. Although domestic cabotage had enabled the national fleet to secure 99.9% of the domestic market, international trade remained heavily dominated by global shipping companies, which controlled more than 90% of export-import cargo. This imbalance produced substantial annual capital outflows, estimated at between IDR 190 trillion and IDR 380 trillion in freight payments. The legal analysis indicated that this underperformance was rooted in regulatory loopholes, particularly ambiguous exemption clauses for foreign vessels, weak enforcement, the absence of integrated real-time data, and high commercial lending rates that constrained domestic fleet expansion. The study concluded that comprehensive regulatory harmonization, stricter exemption criteria, targeted fiscal incentives, and integrated digital maritime supervision were required to safeguard national maritime sovereignty.